A case of reexpansion pulmonary edema and acute pulmonary thromboembolism associated with diffuse large B-cell lymphoma treated with venovenous extracorporeal membrane oxygenation. Issue 1 (January 2021) - Kazama, Shingo; Hiraiwa, Hiroaki; Kimura, Yuki; Ozaki, Reina; Shibata, Naoki; Arao, Yoshihito; Oishi, Hideo; Kato, Hiroo; Kuwayama, Tasuku; Yamaguchi, Shogo; Kondo, Toru; Furusawa, Kenji; et al.
Abstract: A 37-year-old man diagnosed with diffuse large B-cell lymphoma two weeks previously, visited our emergency department with sudden dyspnea. He had a severe respiratory failure with saturated percutaneous oxygen at 80% (room air). Chest radiography showed a large amount of left pleural effusion. After 1000 mL of the effusion was urgently drained, reexpansion pulmonary edema (RPE) occurred. Despite ventilator management, oxygenation did not improve and venovenous extracorporeal membrane oxygenation (VV-ECMO) was initiated in the intensive care unit. The next day, contrast-enhanced computed tomography showed a massive thrombus in the right pulmonary artery, at this point the presence of pulmonary thromboembolism (PTE) was revealed. Fortunately, the patient's condition gradually improved with anticoagulant therapy and VV-ECMO support. VV-ECMO was successfully discontinued on day 4, and chemotherapy was initiated on day 8. We speculated the following mechanism in this case: blood flow to the right lung significantly reduced due to acute massive PTE, and blood flow to the left lung correspondingly increased, which could have caused RPE in the left lung. Therefore, our observations suggest that drainage of pleural effusion when contralateral blood flow is impaired due to acute PTE may increase the risk of RPE. <Learning objective: This is a case of reexpansion pulmonary edema (RPE) in the left lung following acute pulmonary thromboembolism (PTE) in the right lung associated with malignant lymphoma, managed by venovenous extracorporeal membrane oxygenation. Contralateral pleural drainage could increase the risk of RPE because contralateral pulmonary blood flow is assumed to increase when PTE obstructs blood flow. Pleural drainage should be performed carefully in patients with malignant tumors because PTE may be hidden.>